Using SAW, WPM, TOPSIS, AHP for selection of academic administrator roles in public university in Malaysia - Yau’Mee Hayati, Mohamed Yusof; Ruzaini, Abdullah Arshah; Awanis, Romli (Institute of Advanced Scientific Research, 2020)
There are certain qualities and traits needed to be qualified as an Academic Administrator. However, there is a lack of preparation to develop and prevent the loss of leadership and management skills among talented academicians. Lacking this preparation will also lead to the vacancy roles of Academic administrators without occupied. Thus, there is a requirement to have an appropriate model to measure knowledge, skills, and experience among potential academicians during the Talent Development Intervention program. This paper aims to formulate and compare the Multi-criteria Decision-Making methods using Simple Additive Weightage (SAW), Weight Preference Method (WPM), Analytical Hierarchical Priority (AHP), and Technique For Order Performance By Similarity To Ideal Solution (TOPSIS). One set of empirical studies based on the proposed multi-criteria tacit knowledge acquisition model is used to select the best candidate to fill in academic administrator roles. The solution for this case consistent for candidate UITM 1 for majority methods (WPM, AHP and TOPSIS) as the first choice.